Dexamphetamine increased speech and visual unimodal illusions in healthy participants without affecting temporal binding window - Fui Ling, Voon; Sean Janssens, Loffman; Mark Jit Hui, Lim; Joseph W. Y., Lee; Rajan, Iyyalol; Mathew T., Martin-Iverson (Wiley (John Wiley & Sons), 2024)
Objective Stimuli received beyond a very short timeframe, known as temporal binding windows (TBWs), are perceived as separate events. In previous audio-visual multisensory integration (McGurk effect) studies, widening of TBWs has been observed in people with schizophrenia. The present study aimed to determine if dexamphetamine could increase TBWs in unimodal auditory and unimodal visual illusions that may have some validity as experimental models for auditory and visual hallucinations in psychotic disorders.